2013
DOI: 10.1124/dmd.113.051151
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism-Dependent Inhibition of CYP3A4 by Lapatinib: Evidence for Formation of a Metabolic Intermediate Complex with a Nitroso/Oxime Metabolite Formed via a Nitrone Intermediate

Abstract: Metabolism-dependent inhibition (MDI) of cytochrome P450 (P450) enzymes has the potential to cause clinically relevant drug-drug interactions. In the case of several alkylamine drugs, MDI of P450 involves formation of a metabolite that binds quasi-irreversibly to the ferrous heme iron to form a metabolic intermediate (MI) complex. The specific metabolites coordinately bound to ferrous iron and the pathways leading to MI complex formation are the subject of debate. We describe an approach combining heme iron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…An increase in lapatinib serum concentrations and t 1/2 over time was reported with multiple dosing, suggesting time-dependent autoinhibition of lapatinib clearance (Burris et al, 2005). Previous in silico docking and metabolic profiling studies suggested that lapatinib N-dealkylation and N-hydroxylation are predominately catalyzed by CYP3A4, whereas CYP3A5 may preferentially catalyze the O-dealkylation pathway (Takakusa et al, 2011;Chan et al, 2012;Barbara et al, 2013). The results of the present study are consistent with these findings.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…An increase in lapatinib serum concentrations and t 1/2 over time was reported with multiple dosing, suggesting time-dependent autoinhibition of lapatinib clearance (Burris et al, 2005). Previous in silico docking and metabolic profiling studies suggested that lapatinib N-dealkylation and N-hydroxylation are predominately catalyzed by CYP3A4, whereas CYP3A5 may preferentially catalyze the O-dealkylation pathway (Takakusa et al, 2011;Chan et al, 2012;Barbara et al, 2013). The results of the present study are consistent with these findings.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to previous reports, N-dealkylated and N-hydroxylated metabolites were higher by CYP3A4 compared with CYP3A5. The marked decline in the levels of N-OH-LAP during longer incubation times with CYP3A4 may be because N-OH-LAP can be further oxidized to a nitroso intermediate (Takakusa et al, 2011;Barbara et al, 2013). On the other hand, formation of LAP-OH was higher in incubations with CYP3A5 compared with CYP3A4 during longer incubations.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Hence, it is unclear whether the concentration of the parent TDI can be used as a surrogate for the concentration of the metabolite that ultimately complexes with the P450 heme. In addition, MIC formation from alkylamine TDIs may arise from two competing pathways: initial N-dealkylation or N-hydroxylation (Hanson et al, 2010;Barbara et al, 2013). Thus, it is not clear whether inclusion of The unbound fractions (f u ) for the enantiomers of fluoxetine and norfluoxetine in pooled HLMs at 0.1 mg/ml and 1.0 mg/ml microsomal protein and in plasma TABLE 3 Stereospecific risk assessment of the inhibition of CYP2C19 and CYP3A4 after fluoxetine administration…”
Section: Discussionmentioning
confidence: 99%